2021
DOI: 10.1136/bmjspcare-2020-002831
|View full text |Cite
|
Sign up to set email alerts
|

Action plans in idiopathic pulmonary fibrosis: a qualitative study—‘I do what I can do’

Abstract: BackgroundIdiopathic pulmonary fibrosis (IPF) is a progressive, incurable fibrotic lung disease in which patients and caregivers report a high symptom burden. Symptoms are often poorly managed and patients and caregivers struggle to alleviate their distress in the absence of self-management support.AimTo explore perceptions of symptoms, symptom management strategies and self-efficacy for patients with IPF and caregivers who received self-management education and action plans created and provided in a Multidisc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
27
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(27 citation statements)
references
References 32 publications
0
27
0
Order By: Relevance
“…Two of the UK articles presented data from the same interview subjects 23 , 24 two papers were written by the same research group in Denmark 25 , 26 and a further three by a research group in Canada. 27 , 28 All the papers were published between 2013 and 2021 reflecting the increased interest in qualitative research in this field in recent years.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Two of the UK articles presented data from the same interview subjects 23 , 24 two papers were written by the same research group in Denmark 25 , 26 and a further three by a research group in Canada. 27 , 28 All the papers were published between 2013 and 2021 reflecting the increased interest in qualitative research in this field in recent years.…”
Section: Resultsmentioning
confidence: 99%
“…A Canadian study which reviewed the effect of self-management education found that patients were more confident managing their symptoms and able to shift their perspectives to focus on living well with their disease. 27 …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations